극저온 고압액체수소 공급용 인쇄기판 열교환기의 열설계에 관한 연구 - 손상호(SANGHO SOHN); 최병일(BYUNG-IL CHOI) (한국수소 및 신에너지학회 논문집, 2021)
This paper is a study on the thermal design of printed circuit heat exchanger (PCHE) to supply cryogenic high pressure liquid hydrogen stored from hydrogen liquefaction process by using computational fluid dynamics (CFD). This PCHE should be thermally designed to raise the temperature of cryogenic liquid hydrogen to a desired temperature and also to be anti-icing to avoid any local freezing in hot channel. This research presents the effect of inlet velocity and inlet temperature of hydrogen, and the effect of flow configurations of co/counter-flow on thermal design of PCHE heat exchanger based on various CFD simulation analysis.